Is ESG Relevant to Electricity Companies during Pandemics? A Case Study on European Firms during COVID-19 - Boldeanu, Florin Teodor; Clemente-Almendros, José Antonio; Tache, Ileana; Seguí-Amórtegui, Luis (Sustainability, 2022)
The electricity sector was negatively impacted by the coronavirus disease (COVID-19), with considerable declines in consumption in the initial phase. Investors were in turmoil, and stock prices for these companies plummeted. The aim of this paper is to demonstrate the significant negative influence of the pandemic on abnormal returns for the electricity sector, specifically for traditional and renewable companies and the influence of ESG scores, using the event study approach and multi-variate regressions. Our results show that the pandemic indeed had a negative impact on the electricity sector, with renewable electricity companies suffering a sharper decline than traditional ones. Moreover, we find that ESG pillar scores affected electricity companies differently and are sector-specific. For renewable electricity companies, the returns were positively influenced by the environmental ESG scores and negatively by governance ESG scores.
Keywords: ESG scores; COVID; electricity companies; market returns; JCR; Scopus